Lifebox pulse oximeter implementation in Malawi: evaluation of educational outcomes and impact on oxygen desaturation episodes during anaesthesia. (24th April 2017) - Albert, V.; Mndolo, S.; Harrison, E. M.; O'Sullivan, E.; Wilson, I. H.; Walker, I. A.
Summary: Pulse oximetry is an essential monitor for safe anaesthesia but is often not available in low‐income countries. The aim of this study was to determine whether the introduction of pulse oximetry with training was feasible and could reduce the incidence of oxygen desaturation during anaesthesia in a low‐income country. Pulse oximeters were donated, with training, to 83 non‐physician anaesthetists in Malawi. Knowledge was tested immediately before and after training and at follow‐up. Providers were asked to record the lowest peripheral oxygen saturation (SpO2 ) for the first 100 cases anaesthetised after training. The primary clinical outcome was the proportion of cases with an oxygen desaturation event (SpO2 < 90%). Seventy‐seven of 83 (93%) participants completed all pre‐ and post‐training tests. Pulse oximetry knowledge improved after training from a median (IQR [range]) score of 39 (37–42 [28–48]) to 44 (42–46 [35–50]) and this knowledge was maintained for 8 months (p < 0.001). Oxygen saturation data and provider responses were recorded for 4772 cases. The proportion of oxygen desaturation episodes decreased from 17.2% to 6.5%, representing a 36% reduction in the odds of an oxygen desaturation event in the second 50 cases compared with the first 50 (OR 0.64, 95%CI 0.50–0.82, p < 0.001). We conclude that donation of pulse oximeters, with training, in Malawi was feasible, improved knowledge and reduced the incidence of oxygen desaturation events.